A Novel Passive Magnetic Localization Wearable System for Wireless Capsule Endoscopy - Shao, Guoliang; Tang, Yuchao; Tang, Lin; Dai, Qiqi; Guo, Yong-Xin (IEEE sensors journal, 2019)
Magnetic localization provides a feasible way to estimate the position and orientation of the wireless capsule endoscopy embedded with a permanent magnet. However, the magnetic localization suffers from the drifting effect from magnetic noises and the uncertain initial guess during the optimization. In this paper, a localization system with noise cancellation is proposed to reduce the drifting effect of the geomagnetic noise and obtain the initial guess in a simple and effective way. Compared to the prior arts, the proposed system is able to achieve a lower positioning and orientation error under the same system configuration and makes it possible for the patient to move around while wearing the localization system. Besides, the proposed algorithm improves the consistency of positioning error within the localization region. Within a volume of 380 mm by 270 mm by 240 mm covered by 16 digital magnetic sensors, the average positioning error obtained from the proposed algorithm is around 10 mm and the average orientation error is around 12°.